Nexus between stock market capitalization and its Drivers: An ARDL model analysis - Gurung, Rajesh (NCC Journal, 2020)
This paper aims to examine the nexus between the stock market capitalization and it drivers in Nepalese context using the Auto- regressive Distributed Lag (ARDL) approach using the secondary date from 1988/89 to 2018/19. The stock market capitalization is has used as  dependent  variable  and  macro-economic, company  specific, stock market size, government policy, and political factors have been used as independent variables. It has reported the descriptive statistics, correlation analysis, data  stationary, ARDL bound test of long-run relationship. The long-run relationships amongst the variables have been confirmed with the ARDL short-run dynamics and Error Correction Mechanism approaches. The results indicated that gross domestic product and interest rate are important macro-economic variables to explain the stock market capitalization, whereas the return on equity in the case of firm-specific variables. Moreover, both the government policy and political factors have found to influence the stock market capitalization in the context of Nepalese capital market. The findings suggest for a promotion of economic growth with low and stable interest rates, improve company’s return on equity, and implement supportive government policies with political stability to support the overall stability and growth of the country's stock market capitalization.